스트레처블 전극용 나노실버 페이스트 개발 - 남현진; Hyun-jin Nam; 남수용; Su-yong Nam (한국화상학회지, 2020)
신축성 전극은 높은 전도성, 우수한 치수 안정성 및 변형에 대한 낮은 저항 변화를 제공해야 한다. 따라서 본 연구에서는 나노 실버 페이스트를 전도성 물질로 선택하고 신축성 전극을 제작하기 위해 스크린 인쇄법을 사용했다. 두께 125㎛의 PET필름에 탄성 클리어플렉스 폴리우레탄 필름을 경화시킨 후, 블록 이소시아네이트 경화제와 혼합 된 폴리에스텔 수지를 마스킹층으로 코팅하여 필름의 끈적임을 감소시켰다. 롤링볼택 시험으로 폴리에스텔 마스킹층의 효과를 평가하였다. 제조된 투명 클리어플렉스 필름을 신축성 전극기판으로서 사용하였다. 신축성 폴리우레탄 필름 상에 나노실버 페이스트 및 스크린 인쇄 공정을 사용하여 제조된 신축성 전극은 최대 100%의 변형률 범위에서 높은 전도성를 나타냈다. Stretchable electrodes must offer high conductivity, excellent dimensional stability, and low resistance change to strain. In this study, I chose nano silver paste as a conductive material and used a screen printing method to fabricate the stretchable electrode. After curing elastomeric clear flex polyurethane films with a thickness of 125㎛ on PET films, the polyester resin mixed with blocked isocyanate curing agent was coated as a masking layer to reduce the stickiness of the film. The effect of the polyester masking layer was examined using a rolling ball tack test. The prepared clear flex film were used as the stretchable electrode substrates. The stretchable electrodes fabricated by using nano silver paste and screen printing process on the stretchable polyurethane films showed high conductivity in a strain range of up to 100%.